Les premiers pas d'Antun Radić dans l'arene politique croate (1883-1900) - Miloš, Edi (Array, 2008)
Summary: During the last decade of the 19th century Antun Radić gradually ascended the Croatian public life scene. After acquiring a PhD from the University of Zagreb he began his teaching career. He was prominent in writing papers about Croatian and Russian literature and laid the foundations of Croatian ethnology as an editor of a scientific publication entrusted him by the Yugoslav Academy of Sciences and Arts. Simultaneously he displayed an increasing interest in political events taking place in his country struggling to find his place on Croatian political chessboard. There were many signs to indicate he was strongly influenced by the ideas of the Party of Rights since his youth. Nevertheless, Antun Radić long hesitated amid various tendencies and orientations struggling to weaken the power of Ban Khuen-Héderváry and trying to contribute to the reconciliation of the entire Opposition. Gradually he approached "Obzoraši" who finally formed an alliance with "Domovinaši" who emerged;;after the break-up of the Party of Rights. At the same time he was in contact with younger generations, wanting to control the activities of his younger brother Stjepan, one of the leaders of the new generation. As he appeared on the political stage he faced disappointment and a lack of understanding on behalf of representatives of the Croatian intelligentsia. At the break of the 20th century he felt compelled to take his own path in order to impose his own voice